1998
DOI: 10.1021/jp9823502
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Analysis of a Strongly Correlated System, Pentamethine Streptocyanine Dye, Based on Observed Infrared and Raman Spectra and Density Functional Calculations

Abstract: Vibrational analysis is carried out for the organic (cationic) part of a pentamethine streptocyanine dye, [(CH3)2N(CH)5N(CH3)2]+ClO4 - (alias SC5), by measuring its infrared and Raman spectra in solution and in the polycrystalline state and by calculating the vibrational force field and the IR and Raman intensities by the ab initio molecular orbital and density functional methods. It is found that a reasonable set of structural parameters and vibrational force field can be obtained for the SC5 organic part at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
31
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 38 publications
11
31
0
Order By: Relevance
“…It is seen that the calculated vibrational wavenumbers (scaled uniformly by 0.9326, which is obtained by least-squares fitting) and relative IR intensities are in good agreement with the experimental results. It is especially noted that good agreement is obtained for the wavenumber of the strongly IR-active mode in the 1720-1500 cm -1 region, which is sensitive to the computational level as shown in Figure 5 of our previous study 9 for SC5OP. This result supports the validity of using the BHandHLYP functional for calculating the vibrational spectra of this series of molecules.…”
Section: Resultssupporting
confidence: 61%
See 3 more Smart Citations
“…It is seen that the calculated vibrational wavenumbers (scaled uniformly by 0.9326, which is obtained by least-squares fitting) and relative IR intensities are in good agreement with the experimental results. It is especially noted that good agreement is obtained for the wavenumber of the strongly IR-active mode in the 1720-1500 cm -1 region, which is sensitive to the computational level as shown in Figure 5 of our previous study 9 for SC5OP. This result supports the validity of using the BHandHLYP functional for calculating the vibrational spectra of this series of molecules.…”
Section: Resultssupporting
confidence: 61%
“…All the IR bands observed in KBr disk are significantly broader than those observed in solution, and the bands in the 1200-800 cm -1 region are congested and overlap significantly with perchlorate bands, as in the case of the IR spectrum of SC5. 9 However, the decrease in the wavenumber of the strong IR band in the 1800-1400 cm -1 region is clearly seen also in this figure.…”
Section: Resultssupporting
confidence: 54%
See 2 more Smart Citations
“…Full geometry optimizations were made for all the stationary points using the BHandHLYP hybrid HF‐density functionals and the 6‐311G(d,p) basis set. This functional was chosen on the basis of its proven effectiveness 38–49 and because unpublished results from our group have shown that B3LYP functional fails to properly describe H abstraction reactions from sulfur compounds. Zang et al 38 have shown that for proton transfer reactions in multiple hydrogen bond systems, only the hybrid BHandHLYP method (from a large set of DFT methods, including B3LYP) is capable of predicting the structure and energetic information of both the minimum energy and transition structures at a comparable accuracy with the MP2 level.…”
Section: Computational Detailsmentioning
confidence: 99%